Town in a lobster stew - Haywood, B. B. (Thorndike, Me. : Center Point Pub., 2011)
Everyone in town is working frantically for the annual Lobster Stew Cook-Off, the most important event of the year. Mr. Sedley had given elderly Wilma Mae the secret recipe for the award-winning lobster stew with the explicit instruction to hide it carefully. Wilma Mae swears she did exactly that, but now the recipe is missing! Candy, the unofficial town sleuth, decides she'll search for the recipe. But instead of finding a recipe for the stew, she discovers Mr. Sedley's body wrapped in a tarp.
100108
Keywords: City and town life -- Maine; Cooking (Lobsters); Cooking -- Competitions; Murder -- Investigation; Large type books; Maine; Mystery fiction